PEMANFAATAN TEKNOLOGI INFORMASI DALAM PEMBELAJARAN PENDIDIKAN ISLAM - siti seituni (Yayasan Bakti Cendekia Nusantara, 2024)
Information technology has become an essential element in education, including Islamic education, as it provides easy access to information, communication, and interactive, enjoyable learning. This community service discusses how information technology can be effectively integrated into Islamic education, enriching students' learning experiences, accelerating the distribution of teaching materials, and facilitating more effective and efficient interaction between teachers and students. This service utilizes various methods and technological tools that can be integrated into Islamic education. This service's results show that using information technology can increase learning motivation, enrich teaching methods, and facilitate a more objective and measurable evaluation process. This article concludes that the integration of information technology in Islamic education has great potential to support the achievement of educational goals that are more relevant to the needs of the times, provided it is carried out with careful and sustainable planning.